The Primary Cost Drivers of Outpatient Distal Radius Fracture Fixation: A Cost-Minimalization Analysis of 15,379 Cases - Hresko, Andrew M.; Li, Lambert T.; Bokshan, Steven L.; Thirumavalavan, Jeyvikram; Gil, Joseph A. (Journal of Wrist Surgery, 2022)
Background Distal radius fractures are the most common fracture of the upper extremity. While some distal radius fractures can be managed with closed reduction and immobilization, operative treatment is the standard of care, with open reduction internal fixation (ORIF) as a predominant operative method.Questions/Purpose To investigate how patient and surgical characteristics affect the overall costs of internal fixation of distal radius fractures in adults.Patients and Methods The 2014 State Ambulatory Surgery and Services Databases for six states were used to identify cases and surgical characteristics of distal radius fracture ORIF in adult patients.Results Surgical variables that significantly increased cost were postoperative admission within 30 days, regional anesthesia, simultaneous endoscopic carpal tunnel release, and increasing operating room time.Conclusion Substantial contributors to total cost are postoperative hospital admission within 30 days of surgery, use of regional anesthesia, simultaneous endoscopic carpal tunnel release, and longer operative time.Level of Evidence Level III, retrospective cohort study.
Keywords: distal radius; cost drivers; outpatient surgery